Optimising pyrazinamide for the treatment of tuberculosis. Issue 1 (15th July 2021) - Zhang, Nan; Savic, Radojka M.; Boeree, Martin J.; Peloquin, Charles A.; Weiner, Marc; Heinrich, Norbert; Bliven-Sizemore, Erin; Phillips, Patrick P.J.; Hoelscher, Michael; Whitworth, William; Morlock, Glenn; Posey, James; et al.
Pyrazinamide is a potent sterilising agent that shortens the treatment duration needed to cure tuberculosis. It is synergistic with novel and existing drugs for tuberculosis. The dose of pyrazinamide that optimises efficacy while remaining safe is uncertain, as is its potential role in shortening treatment duration further. Pharmacokinetic data, sputum culture, and safety laboratory results were compiled from Tuberculosis Trials Consortium (TBTC) studies 27 and 28 and Pan-African Consortium for the Evaluation of Antituberculosis Antibiotics (PanACEA) multi-arm multi-stage tuberculosis (MAMS-TB), multi-centre phase 2 trials in which participants received rifampicin (range 10–35 mg·kg −1 ), pyrazinamide (range 20–30 mg·kg −1 ), plus two companion drugs. Pyrazinamide pharmacokinetic–pharmacodynamic (PK–PD) and pharmacokinetic-toxicity analyses were performed. In TBTC studies (n=77), higher pyrazinamide maximum concentration (Cmax ) was associated with shorter time to culture conversion (TTCC) and higher probability of 2-month culture conversion (p-value<0.001). Parametric survival analyses showed that relationships varied geographically, with steeper PK–PD relationships seen among non-African than African participants. In PanACEA MAMS-TB (n=363), TTCC decreased as pyrazinamide Cmax increased and varied by rifampicin area under the curve (p-value<0.01). Modelling and simulation suggested that very high doses of pyrazinamide (>4500 mg) or increasing both pyrazinamide and rifampicin would be required to reach targets associated with treatment shortening. Combining all trials, liver toxicity was rare (3.9% with grade 3 or higher liver function tests (LFT)), and no relationship was seen between pyrazinamide Cmax and LFT levels. Pyrazinamide's microbiological efficacy increases with increasing drug concentrations. Optimising pyrazinamide alone, though, is unlikely to be sufficient to allow tuberculosis treatment shortening; rather, rifampicin dose would need to be increased in parallel. The activity of pyrazinamide, a critical drug for tuberculosis treatment, increases as drug concentrations go up, but optimising this drug alone is unlikely to result in treatment shortening. Rather, rifampicin dosing must increase in parallel. https://bit.ly/2KenbHW